A numerical failure analysis of laser micromachining in various thermoplastics - Kaveh, Moghadasi; Khairul Fikri, Tamrin; Nadeem Ahmed, Sheikh; Mohammad, Jawaid (Springer Nature, 2021)
Laser micromachining is one of the promising techniques for mass production of precision miniature parts and microcomponents. However, one primary challenge faced by laser micromachining is the accurate control of processing parameters and optimization. In this work, a numerical study of thermoplastic substrates comprising of polycarbonate (PC), polypropylene (PP), and polymethyl methacrylate (PMMA) materials under laser micromachining was carried out. The thermo-mechanical analysis was developed using finite element based simulations to calculate the stress fields using the accurate temperature map. The laser source was modeled using DFLUX subroutine which uses volumetric heat flux for the Gaussian laser intensity distribution. To simulate the quality of cutting process and quantify kerf characteristics, element failure method based on damage evolution law and Johnson–Cook plasticity model was used to estimate the strain in the elements in the heat-affected zone (HAZ). The simulated results of kerf characteristics and HAZ agree well with the previously published findings. It has been established that with the increase of laser speed, the zone for kerf width and HAZ reduces at a fixed laser power. The vicinity of the cutting zone indicated high-temperature gradients resulting in sharp thermal strains and consequently equivalent von Mises stresses. The variation of stress fields follows the pattern of thermal gradient which is highest near the top surface of the cutting edge and then decays sharply in the neighborhood.